Question

In: Computer Science

The curried version of let f (x,y,z) = (x,(y,z)) is let f (x,(y,z)) = (x,(y,z)) Just...

The curried version of let f (x,y,z) = (x,(y,z)) is

let f (x,(y,z)) = (x,(y,z))

Just f (because f is already curried)

let f x y z = (x,(y,z))

let f x y z = x (y z)

Solutions

Expert Solution

What is Currying?

In mathematics and computer science, currying is the technique of converting a function that takes multiple arguments into a sequence of functions that each take a single argument. For example, currying a function that takes three arguments creates three functions:

For Ex:

Let there be a function which maps as

Currying the above function will produce

Thus maps from to a function which in turn maps from to
The above mathematical expression can also be represented as:

Hence,

Find some more examples below to understand it clearly.

As here, the output is (x,(y,z)), output remains constant while currying.

So, f(x, y, z) becomes f x->y->z-> (x,(y,z))

Ans : Therefore f x y z = (x,(y,z))

Thefore C must be the correct option.


Related Solutions

5. Let X, Y and Z be sets. Let f : X ! Y and g...
5. Let X, Y and Z be sets. Let f : X ! Y and g : Y ! Z functions. (a) (3 Pts.) Show that if g f is an injective function, then f is an injective function. (b) (2 Pts.) Find examples of sets X, Y and Z and functions f : X ! Y and g : Y ! Z such that g f is injective but g is not injective. (c) (3 Pts.) Show that if...
Let f(x,y) be a scalar function, and let F(x,y,z) be a vector field. Only one of...
Let f(x,y) be a scalar function, and let F(x,y,z) be a vector field. Only one of the following expressions is meaningful. Which one? a) grad f x div F b) div(curl(grad f)) c) div(div F) d) curl(div(grad f)) e) grad(curl F)
Let X, Y ⊂ Z and x, y ∈ Z Let A = (X\{x}) ∪ {x}....
Let X, Y ⊂ Z and x, y ∈ Z Let A = (X\{x}) ∪ {x}. a) Prove or disprove: A ⊆ X b) Prove or disprove: X ⊆ A c) Prove or disprove: P(X ∪ Y ) ⊆ P(X) ∪ P(Y ) ∪ P(X ∩ Y ) d) Prove or disprove: P(X) ∪ P(Y ) ∪ P(X ∩ Y ) ⊆ P(X ∪ Y )
Let f: X-->Y and g: Y-->Z be arbitrary maps of sets (a) Show that if f...
Let f: X-->Y and g: Y-->Z be arbitrary maps of sets (a) Show that if f and g are injective then so is the composition g o f (b) Show that if f and g are surjective then so is the composition g o f (c) Show that if f and g are bijective then so is the composition g o f and (g o f)^-1 = g ^ -1 o f ^ -1 (d) Show that f: X-->Y is...
Prove Proposition 6.10 (Let f : X → Y and g : Y → Z be...
Prove Proposition 6.10 (Let f : X → Y and g : Y → Z be one to one and onto functions. Then g ◦ f : X → Z is one to one and onto; and (g ◦ f)−1 = f−1 ◦ g−1 ).
3. Let F : X → Y and G: Y → Z be functions. i. If...
3. Let F : X → Y and G: Y → Z be functions. i. If G ◦ F is injective, then F is injective. ii. If G ◦ F is surjective, then G is surjective. iii. If G ◦ F is constant, then F is constant or G is constant. iv. If F is constant or G is constant, then G ◦ F is constant.
Let f : X → Y and g : Y → Z be functions. We can...
Let f : X → Y and g : Y → Z be functions. We can define the composition of f and g to be the function g◦ f : X → Z for which the image of each x ∈ X is g(f(x)). That is, plug x into f, then plug theresultinto g (justlikecompositioninalgebraandcalculus). (a) If f and g arebothinjective,must g◦ f beinjective? Explain. (b) If f and g arebothsurjective,must g◦ f besurjective? Explain. (c) Suppose g◦ f isinjective....
5) Let the function f : ℝ3 → ℝ3 be given by f(x, y, z) =...
5) Let the function f : ℝ3 → ℝ3 be given by f(x, y, z) = (2x + 2y, 2y + 2z, z + x). a) Prove that f is one to one and onto b) Find the inverse of f, i.e., f−1.
Define f : Z × Z → Z by f(x, y) = x + 2y. (abstract...
Define f : Z × Z → Z by f(x, y) = x + 2y. (abstract algebra) (a) Prove that f is a homomorphism. (b) Find the kernel of f.
Let f: X→Y and g: Y→Z be both onto. Prove that g◦f is an onto function...
Let f: X→Y and g: Y→Z be both onto. Prove that g◦f is an onto function Let f: X→Y and g: Y→Z be both onto. Prove that f◦g is an onto function Let f: X→Y and g: Y→Z be both one to one. Prove that g◦f is an one to one function Let f: X→Y and g: Y→Z be both one to one. Prove that f◦g is an one to one function
ADVERTISEMENT
ADVERTISEMENT
ADVERTISEMENT